Insights into the HIV Latency and the Role of Cytokines - Hokello, Joseph; Lakhikumar Sharma, Adhikarimayum; Dimri, Manjari; Tyagi, Mudit (Pathogens, 2019)
Human immunodeficiency virus-1 (HIV-1) has the ability to infect latently at the level of individual CD4+ cells. Latent HIV-1 proviruses are transcriptionally silent and immunologically inert, but are still capable of reactivating productive lytic infection following cellular activation. These latent viruses are the main obstacle in the eradication of HIV-1, because current HIV-1 treatment regimens are ine ective against them. Normal immunological response against an antigen activates CD4+ naïve T cells. The activated CD4+ naïve T cells undergo cell cycle, resulting in further transformation and profound proliferation to form e ector CD4+ T-cells. Notably, in HIV-1 infected individuals, some of the e ector CD4+ T cells get infected with HIV-1. Upon fulfillment of their e ector functions, almost all activated CD4+ T cells are committed to apoptosis or programmed cell death, but a miniscule fraction revert to quiescence and become resting memory CD4+ T cells to mediate a rapid immunological response against the same antigen in the future. However, due to the quiescent nature of the resting memory T cells, the integrated HIV-1 becomes transcriptionally silent and acquires a latent phenotype. Following re-exposure to the same antigen, memory cells and integrated HIV-1 are stimulated. The reactivated latent HIV provirus subsequently proceeds through its life cycle and eventually leads to the production of new viral progeny. Recently, many strategies against HIV-1 latency have been developed and some of them have even matured to the clinical level, but none can yet e ectively eliminate the latent HIV reservoir, which remains a barrier to HIV-1 cure. Therefore, alternative strategies to eradicate latent HIV need to be considered.
Keywords: HIV-1; latency; eradication; transforming growth factor-beta